Analysis of the Factors Influencing the Intention to Share Information: Word-of-Mouth About Fast-Food Restaurants. - Usiña-Báscones, G. (2024)
In a highly competitive market, word-of-mouth (WOM) has become one of the most effective ways to attract new customers, as consumer opinions are seen as reliable and have a direct impact on their consumption habits. Based on this premise, the present study aimed to analyze the factors that influence fast-food restaurant consumers in Chile in their intention to share word-of-mouth information. A quantitative approach was adopted for this analysis, using a cross-sectional and correlational design, which included 739 Chilean fast-food consumers, who were given a 25-item questionnaire. This questionnaire was developed from previous research in the field and validated by a panel of experts in marketing and research. The data analysis was conducted using the statistical software Smart PLS 4, allowing for the evaluation of the model’s convergent and discriminant validity, as well as facilitating hypothesis testing through structural equation modeling. The results showed that the physical atmosphere of the restaurants generates both hedonic and utilitarian value for consumers, which increases their satisfaction and reinforces their intention to recommend these restaurants. In conclusion, this study provides valuable insights into consumer behavior, offering a solid foundation for strategic decision making that could enhance the positioning of restaurants in the market and create a loyalty cycle among customers.